When push comes to shove: dynamics of unionising in the Israeli high-tech sector. (1st January 2019) - Fisher, Ben; Fisher, Eran
Abstract : This article examines the unprecedented unionising trend among Israeli hightech workers since 2014, based on a field study conducted during 2017-2018. It outlines the concrete constellations that made unionising possible, and the inner dynamics of unionising efforts. It identifies the roots of the trend, maps the different parties involved and analyses the interests, methods and practices that made unionising in this sector possible and even successful.